(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The contribution examines the Italian Pianificazione Condivisa delle Cure within the broader framework of Advance Care Planning as recognized in other legal systems. The aim of the comparative analysis is to underscore the overall significance of these instruments and to identify the distinctive features of Italian legislation, exploring the reasons behind its introduction and potential areas for improvement.